PKK-Turkey War: Implications for Middle East and Turkey - Mr. Sajid Aziz (CISS Insight Journal, 2015)
The Kurdish question can be traced back to the Treaty of Sevres, signed in 1920 between the Ottoman Empire and the Allied forces, which envisaged the creation of a Kurdish state. But the plan was annulled when Young Turks under Kemal Ataturk won the ‘Independence War.’ The resultant Treaty of Lausanne in 1923 not only established the boundaries of modern Turkey but also forced division of Kurdish people in four different countries: Turkey, Iran, Iraq and Syria. The establishment of Turkish Republic was accompanied by a narrowly defined ethno‐linguistic Turkish nationalism and policies of ‘Turkification’, eschewing pluralism and implying forcible assimilation of other ethnic minorities.